Does it pay to study economic sciences? Differences in salaries among graduates of different faculties – evidence from Poland - Pietrzak, Michał (Research Papers of Wrocław University of Economics, 2018)
This paper investigates differences in salaries among 35 th. of graduates of 99 faculties (or equivalent units) in Poland specialized in the field of study “economic sciences” (economics, management, finance, etc.). The study, which is based on data from the Polish Graduates Tracking System (GTS), covers the entire population. First, the ranking of faculties was prepared. It proved that the noticeable differences exist in financial success at the early stage of career of graduates of different faculties. The hypothesis about poorer chances for financial success of graduates from private business schools was denied. Finally the hypothesis about advantage of graduates of faculties located in bigger cities was confirmed. The correlation between city size and salaries is moderately strong
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 515; s. 265-277
Keywords: tertiary education; return on education; economic sciences; graduates; early career; szkolnictwo wyższe; stopa zwrotu z edukacji; nauki ekonomiczne; absolwenci; wczesny etap kariery